"Structural differentiation and the poetics of violence shaping Barack Obama's presidency: a study in personhood, literacy, and the improvisation of African–American publics". (November 2015) - Jackson, Jennifer
Abstract: This paper follows the social role of the United States' logocratic history of citizenship and literacy through education brought to bear as an ideological scaffolding of 'patriotism' in the service of a new, growing, and overt racial poetics of violence against President Barack Obama and, as consequence, the constraints and possibilities to political black publics. This semiotic circulates beyond the 'fringe' and into the interaction of today's politicians, conservative think tanks, mass media pundits, and their consortia of elite special interest groups, lobbies, and markets. Its uptake and recirculation, particularly as massive mediatized everyday language, has brought into relief a narrating register of racial belonging hearkening from the social, political, and legal history of structural subjugation to minorities and black people in the United States since the founding words of its inception. Following the slurs and other tropes of racist talk, images, and memes, the study then examines how these structural histories inform and are used to naturalize an exclusionary rhetoric of violence in an immutable master narrative structuring a shared moral and democratic order. And, it looks to the descriptive violence as well as calls for action, all targeted at President Barack Obama's rupture to this moral order, limiting any arrangements of black collective political agency into improvisational contexts, at best. It follows such differentiation and regulation at two structuring levels: 1) the institutionalization of citizenship; and, 2) civic literacy through formal education of African–Americans. Highlights: Documents racial slurs targeting President Obama and political black publics. Links how logocratic history of the United States informs institutional racism. Evinces how this history is recast to naturalize racial slurs and white supremacy. Frames differentiation at two structuring levels, citizenship and civic literacy.